Blockchain & Cyber Law: A Comprehensive Analysis of Global Literature Trends: Blockchain & Hukum Dunia Maya: Analisis Komprehensif tentang Tren Literatur Global - Chairunnisa, Fahira Safa; Multazam, Mochammad Tanzil; Indakto, Ratro (Proceedings of The ICECRS, 2023)
This research aimed to elucidate the magnitude and relevance of blockchain-related literature, with a focus on cyber law. Data was primarily sourced from the lens.org website, utilizing specific keyword combinations and filtering for 'Journal Articles' related to 'Law'. Analysis of the data revealed the top institutions contributing to blockchain literature, publication trends over time, and the fields of study covered by the most active institutions. Notably, the University of Turin, University of Texas at San Antonio, and University College London emerged as leading contributors. The peak publication years were 2019 and 2020, with Blockchain, Business, and Computer Science being the predominant fields of study. This data holds significant value for understanding the legal implications and potential privacy risks associated with blockchain, especially in Indonesia, and offers insights for future research and regulatory updates in various sectors. Highlights: The University of Turin, University of Texas at San Antonio, and University College London are the leading contributors to blockchain literature. Peak publications on blockchain-related topics occurred in 2019 and 2020. Data offers valuable insights for updating regulations and expanding blockchain technology beyond the financial sector. Keywords: Blockchain Technology, Cyber Law, Scholarly Works, Data Quantification, Methodological Framework